Principles of Salvation Undertaken According to Bible - Agustinus Faot; Jonathan Octavianus; Connie Laurina (Theological Journal Kerugma, 2021)
Various polemics about the concept of salvation confuse God's people. The polemic intended is the difference in understanding of what salvation that can be or cannot be achieved. The problems are not only issues in the world of theology but are also developing in churches in Indonesia. So the concept of salvation developed no longer lies in the Bible but lies in the dogmatics of each church. It must be realized that the Christian faith stands on the basis of the Bible, so the Bible must answer every doctrinal problem. Therefore in this article will provide answers to the polemics of the concept of salvation according to the Bible. This research uses exegesis methodology. The main purpose of this writing is to convince God's people to understand the Bible comprehensively and to understand every concept of Salvation subjectively.